Emotional Ludo game media to improve students' emotional intelligence: a 4D research and development study - Fauziah; Siti Partini Suardiman; Dody Hartanto; Alif Muarifah; Wahyu Nanda Eka Saputra; Muya Barida; Akhmad Fajar Prasetya; Agus Ria Kumara; Hardi Santosa (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
This study was conducted with the aim of developing guidance and counseling media in the form of a ludo game with emotional themes. The research methods used in this study were Research and Development (R&D). The 4-D model development concept, which consists of four stages of development such as Define, Design, Development, and Dissemination. The participants in this study were 8 students from class XI of SMAN 1 Baros who had low levels of emotional intelligence. Data collection techniques were performed using a questionnaire instrument. The feasibility test of the developed product obtained a score of 94% in the material feasibility test, 81% in the language feasibility test, and 91.66% in the media expert feasibility test, resulting in an average score of 91% or falling into the “Highly Appropriate” category. Furthermore, based on the students' responses to the game media, the score was 84%, which falls into the “excellent” category. This indicates that the development of the emotional Ludo game media product can be implemented for users. The components of the product package include a board game, four versions of game cards, a game guidebook, dice, a dice shaker, game pieces, and game packaging.